HRSA's PEPFAR-Supported Resilient and Responsive Health Systems Initiative in Liberia. Issue 1 (8th October 2021) - Tidwell, George; Razak, Myat Htoo
During the 2014-16 Ebola outbreak, Liberia suffered 2, 544 deaths, including 8% of its doctors, nurses and midwives. The Government responded in 2016 with a seven–year Health Workforce Program (HWP), the goal of which was "the creation of a fit-for-purpose, motivated, and highly-skilled workforce." The US Health Resources and Services Administration (HRSA) with the support from the US President's Emergency Plan for AIDS Relief (PEPFAR), established Resilient and Responsive Health Systems project to assist Liberia in strengthening health workforce and health systems. As the HWP approaches its final year, progress the numbers and skills of physicians, nurses and midwives have improved, through national and global support, and there have been some improvements in the overall health system. Improving health for everyone in Liberia is an ongoing process that requires continuing support and collaboration from national and global partners including US government agencies, UN agencies, academic and training institutions, private foundations, regional networks, and especially the people of Liberia.